2016
DOI: 10.5430/cns.v4n4p23
|View full text |Cite
|
Sign up to set email alerts
|

“As long as you need me I’m yours.” Caregiving for a pediatric cancer survivor

Abstract: A pediatric cancer diagnosis is devastating -to children, as well as their families. Children experience a variety of negative effects, whether physical, cognitive, and/or emotional, and often face continued or newly developed effects l past remission termed late effects. However, it is imperative to note that support persons, or caregivers of survivors of pediatric cancer, are also affected by their caregiver roles as they help their survivors cope with their late effects. This study aimed to understand how c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, the help given to these mothers by their family and friends helped ease some of the stresses of caring for their children and families during the periods of their children’s treatment. While some of the literature addresses the type of support that families receive from friends and extended family members (Clarke et al, 2005; Fletcher, 2011), past literature has revealed that mothers of children with cancer become more appreciative of their families and friends during, and after their children’s treatment (Fletcher, 2011; Molinaro & Fletcher, 2016). The mothers in this work admitted to receiving help with transportation, meal cooking and planning, and childcare and babysitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the help given to these mothers by their family and friends helped ease some of the stresses of caring for their children and families during the periods of their children’s treatment. While some of the literature addresses the type of support that families receive from friends and extended family members (Clarke et al, 2005; Fletcher, 2011), past literature has revealed that mothers of children with cancer become more appreciative of their families and friends during, and after their children’s treatment (Fletcher, 2011; Molinaro & Fletcher, 2016). The mothers in this work admitted to receiving help with transportation, meal cooking and planning, and childcare and babysitting.…”
Section: Discussionmentioning
confidence: 99%
“…As such, children often experience physical, psychological, and social effects as a result of their pediatric cancer journeys (Canadian Cancer Society, 2008; Childhood Cancer Canada Foundation, 2011). Their family members also experience a variety of effects that may last beyond the treatment phases and into remission (Fletcher, 2010, 2011; Molinaro & Fletcher, 2016). For example, parents in both qualitative and quantitative research have reported the high levels of stress and fatigue experienced during pediatric cancer treatment, in addition to relationship issues with their spouses (Björk, Wiebe, & Hallström, 2009; Fletcher, 2010; Klassen et al, 2012; Patterson, Holm, & Gurney, 2004).…”
Section: Introductionmentioning
confidence: 99%